Sistem Informasi Keuangan Dalam Meningkatkan Akuntabilitas Desa - Gunawan, Putri Dinda; Animah, Animah; Isnawati, Isnawati (E-Jurnal Akuntansi; Vol 32 No 7 (2022)DO - 10.24843/EJA.2022.v32.i07.p16, 2022)
The purpose of this research is to find out how the implementation of financial information system in increasing accountability in Batuyang village. This research is a descriptive type of research. The informants involved were the Head of Batuyang Village, Treasurer of Batuyang Village, Secretary of Batuyang Village, Head of Pringgabaya Sub-district, Head of BPD Batuyang Village, with a total of five informants. Data was collected by using interview, documentation and observation techniques. The results of this study are related to the implementation of a financial information system in increasing accountability in Batuyang Village which has been effective and helps in increasing the accountability of the Batuyang village government both vertically and horizontally. This can be seen from the five indicators that have been fulfilled by the Batuyang village government, namely the suitability of the information requested in the template/program, the suitability of the type of report, the accuracy and certainty of reporting time, the conformity of the requirements and reporting procedures, and feedback. The implications of this research can be taken into consideration for decision making by the Batuyang Village government in the application of the village financial information system. Keywords: Financial Information System; Accountability; Village Government; Effectiveness Measurement Parameters.